Devotion to Sri Krishna - Mumbai Archive Project Team (Jio Institute, 2024)
Devotion to Sri Krishna as svayam bhagavan (the Supreme God) is central to the Bhakti movement, which has left an indelible mark on Hinduism and the cultural and spiritual landscape of India.